Accumulator three phase converter - Mikulka, Martin; Háze, Jiří (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2022)
The paper presents description of design of a voltage converter and a 3-phase inverter with smart LCD controller. The LCD control terminal communicates via proprietary CAN interface. The final converter can supply a 3-phase output voltage with a selectable waveform, but primarily a harmonic sinusoidal (user configurable via terminal). The inverter will have an adjustable voltage (sinusoidal amplitude) in a certain range which is configured by user via control terminal also. It provides the possibility of a small correction of the output frequency and phase shift so that it can generate, for example, a two-phase 120 V grid and others.
Keywords: DC / DC converter, 3-phase inverter, DC / AC inverter, STM32, switched converters, digital control, ethernet, CAN, frequency waveform generation, powerful converter